Silicone elastomers filled with rare earth oxides - Mihail Iacob; Anton Airinei; Mihai Asandulesa; Mihaela Dascalu; Nita Tudorachi; Leonor Hernandez; Maria Cazacu (Materials Research Express, 2020)
Silicones which possess, amongst others, remarkable mechanical properties, thermal stability over a wide range of temperatures and processability, and rare earth oxides (REO), known for their unique optic, magnetic and catalytic properties can be coupled into multifunctional composite materials (S-REOs). In addition, the intrinsic hydrophobicity of REO and polysiloxanes makes them easily compatible without the need for surface treatments of the former. Thus, europium oxide (Eu _2 O _3 ), gadolinium oxide (Gd _2 O _3 ) and dysprosium oxide (Dy _2 O _3 ) in amounts of 20 pph are incorporated as fillers into silicone matrices, followed by processing mixture as thin films and crosslinking at room temperature. The analysis of the obtained films reveals the changes induced by these fillers in the thermal, mechanical, dielectric and optical properties, as well as the hydrophobicity of the silicones. The luminescence properties of S-REO composites were investigated by fluorescence spectra and lifetime - resolved measurements with a multiemission peaks from blue to greenish register. The thermogravimetrical analysis indicates an increasing of thermal stability of the composites that contain REO, compared to pure silicone. As expected, the dielectric permittivity significantly increased due to nature of the fillers, while the dielectric loss values are relatively low for all samples, indicating a minimal conversion of electrical energy in the form of heat within bulk composites. The presence of rare earth oxides into the silicone matrix facilitates the motions of long-range charge carriers through the network resulting in higher values of conductivity of the composite films. The stress-strain measurements revealed the reinforcing effect of the rare earth metal oxides on a silicone matrix, leading to a significant increase of Young modulus. The known hydrophobicity of silicones is further enhanced by the presence of REO.